Chorioamnionitis Causes Kidney Inflammation, Podocyte Damage, and Pro-fibrotic Changes in Fetal Lambs - Hoogenboom, Lieke A.; Lely, A. Titia; Kemp, Matthew W.; Saito, Masatoshi; Jobe, Alan H.; Wolfs, Tim G. A. M.; Schreuder, Michiel F. (Frontiers in Pediatrics, 2022)
Background Perinatal complications, such as prematurity and intrauterine growth restriction, are associated with increased risk of chronic kidney disease. Although often associated with reduced nephron endowment, there is also evidence of increased susceptibility for sclerotic changes and podocyte alterations. Preterm birth is frequently associated with chorioamnionitis, though studies regarding the effect of chorioamnionitis on the kidney are scarce. In this study, we aim to unravel the consequences of premature birth and/or perinatal inflammation on kidney development using an ovine model. Methods In a preterm sheep model, chorioamnionitis was induced by intra-amniotic injection of lipopolysaccharide (LPS) at either 2, 8 or 15 days prior to delivery. Control animals received intra-amniotic injections of sterile saline. All lambs were surgically delivered at 125 days’ gestation (full term is 150 d) and immediately euthanized for necropsy. Kidneys were harvested and processed for staining with myeloperoxidase (MPO), Wilms tumor-1 (WT1) and alpha-smooth muscle actine (aSMA). mRNA expression of tumor necrosis factor alpha (TNFA), Interleukin 10 (IL10), desmin (DES), Platelet derived growth factor beta (PDGFB), Platelet derived growth factor receptor beta (PDGFRB), synaptopodin (SYNPO) and transforming growth factor beta (TGFB) was measured using quantitative PCR. Results Animals with extended (but not acute) LPS exposure had an inflammatory response in the kidney. MPO staining was significantly increased after 8 and 15 days (p=0.003 and p=0.008, respectively). Expression of TNFA (p=0.016) and IL10 (p=0.026) transcripts was increased, peaking on day 8 after LPS exposure. Glomerular aSMA and expression of TGFB was increased on day 8, suggesting pro-fibrotic mesangial activation, however this was not confirmed with PDFGB or PDGFRB.The number of WT1 positive nuclei in the glomerulus, as well as expression of synaptopodin, decreased, indicating podocyte injury. Conclusion We report that, in an ovine model of prematurity, LPS-induced chorioamnionitis leads to inflammation of the immature kidney. In addition, this process was associated with podocyte injury and there are markers to support pro-fibrotic changes to the glomerular mesangium . These data suggest a potential important role for antenatal inflammation in the development of preterm-associated kidney disease, which is frequent.